2018
DOI: 10.2217/cns-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

Rapid infusion rituximab is well tolerated in patients with primary CNS lymphoma

Abstract: Aim:To establish the safety and feasibility of rapidly infusing rituximab over 90 min in patients with primary CNS lymphoma (PCNSL).Patients & methods:We retrospectively reviewed all patients with PCNSL who received rapid rituximab infusions (RRI) from January 2016 to January 2017. Primary end point was incidence of infusion reactions.Results & conclusion:11 patients received a total of 44 RRIs. Rituximab was dosed at 500 or 750 mg/m2. Premedication included acetaminophen and diphenhydramine. No infusion react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Utilizing chart review to analyze infusion reactions with the rapid protocol, none of the studies found a statistically significant increase in reaction rates when compared to patients receiving the standard protocol 17,20–21. Interestingly, many of the studies within this review found reaction rates to be lower with the rapid protocol than with the standard protocol,17,19,21 with 2 of the studies showing zero infusion reactions with the rapid protocol 18,20. This evidence overwhelmingly supports the idea that rapid rituximab infusion is safe.…”
Section: Results Of the Reviewmentioning
confidence: 88%
“…Utilizing chart review to analyze infusion reactions with the rapid protocol, none of the studies found a statistically significant increase in reaction rates when compared to patients receiving the standard protocol 17,20–21. Interestingly, many of the studies within this review found reaction rates to be lower with the rapid protocol than with the standard protocol,17,19,21 with 2 of the studies showing zero infusion reactions with the rapid protocol 18,20. This evidence overwhelmingly supports the idea that rapid rituximab infusion is safe.…”
Section: Results Of the Reviewmentioning
confidence: 88%
“…infusions of rituximab have previously been administered at a dose of 375 mg/m 2 . Recently, rapid infusion of rituximab at doses ranging from 500–750 mg/m 2 were administered in a cohort of 11 patients with primary central nervous system lymphoma and no IRRs of any grade were observed during the 44 rapid rituximab infusions 31 . In our cohort, patients with CLL were treated with SDZ‐RTX‐chlorambucil or SDZ‐RTX‐venetoclax, both with rituximab at a dose of 500 mg/m 2 32,33 .…”
Section: Discussionmentioning
confidence: 95%
“…Recently, rapid infusion of rituximab at doses ranging from 500–750 mg/m 2 were administered in a cohort of 11 patients with primary central nervous system lymphoma and no IRRs of any grade were observed during the 44 rapid rituximab infusions. 31 In our cohort, patients with CLL were treated with SDZ‐RTX‐chlorambucil or SDZ‐RTX‐venetoclax, both with rituximab at a dose of 500 mg/m 2 . 32 , 33 Our data show that patients with CLL fulfilling our inclusion and exclusion criteria (in particular, lymphocytosis <5 × 10 9 /L and prior tolerance of a standard rituximab i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions outlined in Table 1 provide practical recommendations which can be implemented to meet the needs of patients during the dynamics of a pandemic. 550…”
Section: Altering System Cancer Regimensmentioning
confidence: 99%
“…56 Rapid infusion protocols have also been described for daratumumab administered as a 90-minute infusion and bevacizumab over 10-minutes with no added safety signals. [25][26][27][28]34,36 To further reduce infusion times, various subcutaneous options have emerged that allow administration times of a few minutes. Rituximab hyaluronidase, trastuzumab hyaluronidase, and most recently, daratumumab hyaluronidase are subcutaneous injections that can be delivered in under 10 minutes.…”
Section: Extending Therapeutic Intervals and Minimizing Chair Timementioning
confidence: 99%